Liberation, national unity, and the politics of limited reform: Part 1: Italy, 1944-1948 - Stadler, Alfred William (My University, 1993)
Italy from the mid to late 1940s provides a classic instance of a massive uprising by the poorest elements in society in support of fundamental changes in their condition. The efforts of the Italian industrial working class and the peasantry through strike action, land seizures and military action in the Resistance, were supported by the unions and by the Socialist and Communist parties. But the political project for fundamental reform was undermined in the post-liberation settlement. The great wave of mobilisation generated during the mid-1940s subsided for a variety of reasons. With its subsidence, the hopes of fundamental change which had inspired many to risk their lives in the revolt against fascism and the German occupation declined. Italy's subsequent history was one of economic growth, but it was purchased at the expense of basic reforms on the land, in industry and the state. Of course things did not go back to where they had stood in 1944. Conservatives opposed to Fascism formed the Christian Democratic Party in 1943. They enjoyed enough credibility to assume a leading position in the anti-fascist coalition which assumed office once the enfeebled Badoglio government had given way to a more representative provisional government. The Christian Democrats (DC) used their authority to consolidate an alliance which stretched across Italian party politics from the Resistance, Communists, Socialists and Liberals, to unions and business associations. The effect of Christian Democratic hegemony was to undermine the most radical elements in the coalition. But they made sufficient concessions to pressures for change from the peasantry and the working class to contain them, and thus to ensure major continuities with the social, economic and political status quo ante. These concessions were important in maintaining their hegemony: each time Christian Democratic policy shifted markedly to the right they experienced rather rapid deflations in electoral support.
African Studies Seminar series. Paper presented 9 August 1993
Keywords: Italy. Politics and government, 1943-1947; Italy. History, 1945-1976